A zinc oxide / in-situ fluorine-doped nickel oxide composite material and its preparation method and application
By using zinc oxide/in-situ fluorine doped nickel oxide composite in NO2 sensors, the problems of sensor baseline resistance drift and gas sensitivity suppression in high humidity environments are solved, and high sensitivity and humidity resistance stability are achieved under a wide range of conditions.
Patent Information
- Application Number
- CN202411221857.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-09-02
AI Technical Summary
Existing NO2 sensors exhibit problems of baseline resistance drift and gas-sensitive sensitivity suppression in high humidity environments, resulting in significant deterioration of the gas-sensitive performance of the material.
The zinc oxide/in-situ fluorine-doped nickel oxide composite material is used to achieve in-situ doping of fluorine ions into nickel oxide through solvothermal reaction and annealing treatment process, forming a nanostructure with high specific surface area and good gas-sensitive properties.
Under a wide range of operating temperatures and relative humidity conditions, the material exhibits high sensitivity, high selectivity and excellent humidity resistance stability, and the detection accuracy of NO2 is not affected by ambient humidity.
Smart Images

Figure CN119100471B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of gas-sensitive materials and relates to a zinc oxide / in-situ fluorine-doped nickel oxide composite material and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] The most commonly used and widely researched NO2 sensor is the resistive semiconductor metal oxide gas sensor, which works by using the electron exchange between the material and the gas molecules to be measured, causing the energy band bending of the semiconductor metal oxide material, changes in the carrier concentration and resistance, and then showing a response to the gas to be measured. However, the actual working environment of NO2 sensors currently often has problems such as high humidity and variable humidity values. When traditional semiconductor metal oxide sensors are exposed to high humidity, active oxygen on the surface of the material will react with water molecules, forming stable surface hydroxyl groups on the gas-sensitive active sites of the material, while releasing free electrons to the conduction band of the material, changing the carrier concentration of the material and occupying the gas-sensitive adsorption sites of the material, causing serious baseline resistance drift and gas-sensitive sensitivity suppression, resulting in a significant deterioration in the gas-sensitive performance of the material under high humidity. Summary of the invention
[0004] In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide a zinc oxide / in-situ fluorine-doped nickel oxide composite material and a preparation method and application thereof. The composite material prepared by the present invention utilizes its unique morphology and structure, and through the high hygroscopicity of nickel oxide and the strong electronegative fluorine ion doping effect, significantly inhibits the interference of water molecules on the active sites of the material and the formation of surface hydroxyls, and successfully realizes humidity-independent, highly sensitive and highly selective NO2 detection under a wide range of operating temperatures and relative humidity conditions, and has excellent practical application value and prospects for industrial production.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] In a first aspect, a method for preparing a zinc oxide / in-situ fluorine-doped nickel oxide composite material comprises the following steps:
[0007] Hydroxyzinc fluoride, a nickel source, an alkali source and a surfactant are added to an alcohol solvent, mixed evenly and then subjected to a solvothermal reaction to obtain a hydroxyzinc fluoride / nickel hydroxide precursor, and the hydroxyzinc fluoride / nickel hydroxide precursor is annealed to thermally decompose the hydroxyzinc fluoride / nickel hydroxide precursor to obtain the product.
[0008] In the solvent thermal reaction process of the present invention, nickel ions and hydroxide ions are combined to form nickel hydroxide, and the surfactant reduces the surface energy of hydroxy zinc fluoride to avoid spontaneous agglomeration of nickel hydroxide, and the nickel hydroxide is uniformly dispersed on the surface of hydroxy zinc fluoride in the form of nanoparticles; in the annealing process, both hydroxy zinc fluoride and nickel hydroxide are pyrolyzed, wherein hydroxy zinc fluoride is pyrolyzed to produce zinc oxide and hydrogen fluoride, and nickel hydroxide is pyrolyzed to produce nickel oxide. In the process of pyrolyzing to produce zinc oxide and nickel oxide, since nickel hydroxide is uniformly dispersed on the surface of hydroxy zinc fluoride, hydrogen fluoride generated by pyrolyzing zinc fluoride can not only adjust the morphology of zinc oxide when diffusing outward, but also easily contact nickel hydroxide and / or nickel oxide, so that the decomposed fluoride ions can enter the lattice of nickel oxide during the formation of nickel oxide, and then the decomposed fluorine is in-situ doped into NiO, that is, the selective doping of F ions to NiO is achieved.
[0009] At the same time, the position of the in-situ fluorine-doped nickel oxide on zinc oxide after pyrolysis remains basically unchanged relative to that before pyrolysis, that is, the in-situ fluorine-doped nickel oxide can be evenly dispersed on the surface of zinc oxide. This structure is beneficial for providing more gas-sensitive reaction sites and diffusion paths, which helps to improve the gas-sensitive performance. The nickel oxide structure evenly dispersed on the surface can avoid occupying a large number of active sites of zinc oxide and avoiding the inhibition of gas-sensitive performance. At the same time, a heterogeneous interface is formed between the zinc oxide and nickel oxide components, which promotes surface interface electron transfer and provides more reactive free electrons for the NO2 gas-sensitive reaction, which helps to improve the gas-sensitive performance.
[0010] In a second aspect, a zinc oxide / in-situ fluorine-doped nickel oxide composite material is obtained by the above preparation method.
[0011] In the composite material obtained by the above preparation method, the zinc oxide matrix is assembled into a three-dimensional radial snowflake shape by zinc oxide nanoparticles, and in-situ fluorine-doped nickel oxide nanoparticles are dispersed on the surface of the zinc oxide matrix.
[0012] Among them, zinc oxide is an n-type semiconductor with high conductivity and narrow band gap. As the matrix of the composite material, it provides the main gas-sensitive reaction sites. The large gaps between zinc oxide nanoparticles provide channels for gas diffusion. Nickel oxide is a p-type semiconductor with high hygroscopicity. In situ fluorine-doped nickel oxide is highly dispersed on the surface of zinc oxide in the form of nanoparticles, which can make water molecules preferentially adsorbed on the in situ fluorine-doped nickel oxide, avoiding the influence of water molecules on the gas-sensitive active sites on the surface of zinc oxide and inhibiting the formation of surface hydroxyl groups. Fluoride ion dopants can optimize the electronic structure and surface electronegativity of nickel oxide, reduce the relative energy level position of nickel oxide, inhibit the amount of surface chemically adsorbed oxygen and inhibit the formation of surface hydroxyl groups on nickel oxide, thereby avoiding the "overflow" of water molecules into the zinc oxide matrix after the hydrophilic nickel oxide surface hydroxyl groups are saturated and the deterioration of the humidity stability of the sensing material.
[0013] In a third aspect, a gas sensor comprises a substrate, a sensing layer is arranged on the surface of the substrate, and the gas sensitive material of the sensing layer is the above zinc oxide / in-situ fluorine-doped nickel oxide composite material.
[0014] In a fourth aspect, an application of the above zinc oxide / in-situ fluorine-doped nickel oxide composite material or gas sensor in detecting NO2.
[0015] The beneficial effects of the present invention are:
[0016] (1) The present invention utilizes solvent thermal synthesis and annealing treatment processes to achieve uniform loading of zinc oxide by in-situ fluorine-doped nickel oxide components. The composite material system effectively utilizes the high hydrophilicity of the nickel oxide component to achieve preferential adsorption of water molecules under high humidity conditions, thereby avoiding interference of water molecules with the main gas-sensitive active sites of the zinc oxide matrix. In-situ fluorine ion doping is utilized to increase the surface electronegativity and relative position of the energy levels of the nickel oxide component, thereby inhibiting the formation of a large number of hydroxyl groups on the surface of the nickel oxide, thereby avoiding the "overflow" of hydroxyl groups on the surface of the hydrophilic second phase oxide to the surface of the zinc oxide matrix, thereby further deteriorating the humidity stability of the material.
[0017] (2) During the annealing process of the preparation method of the present invention, the fluorine decomposed from hydroxyzinc fluoride can not only adjust the morphology of the formed zinc oxide, but also can be selectively in-situ doped into the NiO lattice, thereby avoiding the doping of ZnO by external fluorine sources. The preparation process is simple and ingenious.
[0018] (3) The zinc oxide / in-situ fluorine-doped nickel oxide composite material prepared by the present invention has a flower-shaped zinc oxide matrix assembled from nanorods stacked with nanoparticles. This unique microscopic morphology significantly increases the specific surface area of the material, and the large number of gaps between the nanoparticles provide a large number of diffusion channels for the gas to be measured, which can effectively improve the gas sensitivity and response recovery speed of the material.
[0019] (4) The zinc oxide / in-situ fluorine-doped nickel oxide composite material prepared by the present invention exhibits excellent humidity resistance stability in the detection of NO2. The response value to 10 ppm NO2 at 80% RH and 200°C can reach 8.06. Compared with the dry test environment (30% RH), the response value can be maintained above 99%, which can effectively ensure that the NO2 detection accuracy of the material under the dynamic humidity conditions of actual work will not be affected by the environmental humidity error. At the same time, it can still show excellent selectivity in the detection of NO2 under high environmental humidity conditions, which can effectively avoid the gas-sensitive material being affected by other interfering gases in the detection of NO2.
[0020] (5) The zinc oxide / in-situ fluorine-doped nickel oxide composite material prepared by the present invention exhibits excellent humidity stability for the detection of NO2 under a wide range of working temperature conditions. In the optimal combination within the working temperature range of 100-240°C, there is almost no response value change and baseline resistance drift when detecting NO2, which indicates that the material can accurately detect NO2 under a wide working temperature and dynamic ambient humidity conditions to meet the needs of different actual working environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0022] Figure 1 XRD patterns of the hydroxy zinc fluoride precursor, pure zinc oxide and zinc oxide / in-situ fluorine-doped nickel oxide composite materials prepared in Examples 1-6 of the present invention; wherein, a is the XRD pattern of the hydroxy zinc fluoride precursor, pure zinc oxide and zinc oxide / in-situ fluorine-doped nickel oxide composite materials prepared in Examples 1-6 of the present invention; b is the enlarged XRD pattern of the pure zinc oxide and zinc oxide / in-situ fluorine-doped nickel oxide composite materials prepared in Examples 2-6 of the present invention.
[0023] Figure 2 SEM images of the hydroxy zinc fluoride precursor, pure zinc oxide and zinc oxide / in-situ fluorine-doped nickel oxide composite material prepared in Examples 1-6 of the present invention; wherein, a1 and a2 are SEM images of the hydroxy zinc fluoride precursor prepared in Example 1; b1 and b2 are SEM images of the pure zinc oxide material prepared in Example 2; c1 and c2 are SEM images of the zinc oxide / in-situ fluorine-doped nickel oxide composite material prepared in Example 3; d1 and d2 are SEM images of the zinc oxide / in-situ fluorine-doped nickel oxide composite material prepared in Example 4; e1 and e2 are SEM images of the zinc oxide / in-situ fluorine-doped nickel oxide composite material prepared in Example 5; f1 and f2 are SEM images of the zinc oxide / in-situ fluorine-doped nickel oxide composite material prepared in Example 6;
[0024] Figure 3TEM, HRTEM and HAADF-STEM spectra of pure zinc oxide and zinc oxide / in-situ fluorine-doped nickel oxide composite materials prepared in Examples 2 and 4 of the present invention; wherein, a and b are TEM images of pure zinc oxide prepared in Example 2, and the small image in b is a selected area electron diffraction image; c is an HRTEM image of pure zinc oxide prepared in Example 2; c1 and c2 are the interplanar spacing values measured in c; d and e are TEM images of zinc oxide / in-situ fluorine-doped nickel oxide composite materials prepared in Example 4, f is an HRTEM image of zinc oxide / in-situ fluorine-doped nickel oxide composite materials prepared in Example 4, f1 and f2 are the interplanar spacing values measured in Figure c; g1 is the HAADF-STEM image of the zinc oxide / in-situ fluorine-doped nickel oxide composite material prepared in Example 4, and g2, g3, g4, and g5 are surface distribution images of Zn, O, Ni and F elements, respectively.
[0025] Figure 4 The XPS spectra of pure zinc oxide, zinc oxide / in-situ fluorine-doped nickel oxide composite materials and fluorine-free doped nickel oxide / zinc oxide composite materials prepared in Examples 2-7 of the present invention; wherein, a is the Zn 2p fine spectrum of pure zinc oxide, zinc oxide / in-situ fluorine-doped nickel oxide composite materials and fluorine-free doped nickel oxide / zinc oxide composite materials prepared in Examples 2, 4 and 7; b is the F1s fine spectrum of pure zinc oxide and zinc oxide / in-situ fluorine-doped nickel oxide composite materials prepared in Examples 2-7; c is the O1s fine spectrum of pure zinc oxide and zinc oxide / in-situ fluorine-doped nickel oxide composite materials prepared in Examples 2-7; d is the Ni 2p fine spectrum of pure zinc oxide and zinc oxide / in-situ fluorine-doped nickel oxide composite materials prepared in Examples 2-7.
[0026] Figure 5 The BET-BJH spectra of pure zinc oxide, zinc oxide / in-situ fluorine-doped nickel oxide composite materials and fluorine-free nickel oxide / zinc oxide composite materials prepared in Examples 2, 4 and 7 of the present invention; wherein a is the BET-BJH spectrum of pure zinc oxide prepared in Example 2; b is the BET-BJH spectrum of zinc oxide / in-situ fluorine-doped nickel oxide composite materials prepared in Example 4; c is the BET-BJH spectrum of fluorine-free nickel oxide / zinc oxide composite materials prepared in Example 7.
[0027] Figure 6 The O2-TPD spectra of pure zinc oxide, zinc oxide / in-situ fluorine-doped nickel oxide composite materials and fluorine-free nickel oxide / zinc oxide composite materials prepared in Examples 2, 4 and 7 of the present invention.
[0028] Figure 7 NO2-TPD spectra of pure zinc oxide, zinc oxide / in-situ fluorine-doped nickel oxide composite materials and fluorine-free nickel oxide / zinc oxide composite materials prepared in Examples 2, 4 and 7 of the present invention.
[0029] Figure 8 It is the Quasi-XPS spectrum of the zinc oxide / in-situ fluorine-doped nickel oxide composite material prepared in Example 4 of the present invention; wherein, a is the Zn 2p spectrum of the zinc oxide / in-situ fluorine-doped nickel oxide composite material prepared in Example 4; b is the F1s spectrum of the zinc oxide / in-situ fluorine-doped nickel oxide composite material prepared in Example 4; c is the O1s spectrum of the zinc oxide / in-situ fluorine-doped nickel oxide composite material prepared in Example 4; d is the Ni 2p spectrum of the zinc oxide / in-situ fluorine-doped nickel oxide composite material prepared in Example 4.
[0030] Fig. 9 These are the response recovery resistance change curves of the pure zinc oxide, zinc oxide / in-situ fluorine-doped nickel oxide composite material and non-fluorine-doped nickel oxide / zinc oxide composite material prepared in Examples 2-7 of the present invention to 10 ppm NO2 at 200°C and 30-80% RH.
[0031] Fig.10 The following is a resistance recovery curve of the zinc oxide / in-situ fluorine-doped nickel oxide composite material prepared in Example 4 of the present invention in response to 10ppm NO2 at 100-240°C and 30-80% RH; wherein a is the resistance recovery curve of the zinc oxide / in-situ fluorine-doped nickel oxide composite material at 100°C and 30-80% RH to 10ppm NO2; b is the resistance recovery curve of the zinc oxide / in-situ fluorine-doped nickel oxide composite material at 160°C and 30-80% RH to 10ppm NO2; c is the resistance recovery curve of the zinc oxide / in-situ fluorine-doped nickel oxide composite material at 200°C and 30-80% RH to 10ppm NO2; and d is the resistance recovery curve of the zinc oxide / in-situ fluorine-doped nickel oxide composite material at 240°C and 30-80% RH to 10ppm NO2.
[0032] Fig.11 The present invention provides a zinc oxide / in-situ fluorine-doped nickel oxide composite material prepared in Example 4 of the present invention, and a response recovery resistance change curve, a response value-concentration relationship and a corresponding fitting curve at 200°C, 30% and 80% RH to 0.1-20ppm NO2; wherein, a is the response recovery resistance change curve of the zinc oxide / in-situ fluorine-doped nickel oxide composite material prepared in Example 4 to 0.1-20ppm NO2 at 200°C, 30%, 80% RH; b is the response value-concentration relationship and the corresponding fitting curve.
[0033] Fig.12 This is the cycle curve of the zinc oxide / in-situ fluorine-doped nickel oxide composite material prepared in Example 4 of the present invention to 10 ppm NO2 at 200°C, 30% and 80% RH.
[0034] Fig.13It is the response value of the zinc oxide / in-situ fluorine-doped nickel oxide composite material prepared in Example 4 of the present invention to 10 ppm of different types of test gases at 200°C, 30% and 80% RH; wherein, a is the response value of the zinc oxide / in-situ fluorine-doped nickel oxide composite material prepared in Example 4 to 10 ppm of different types of test gases at 200°C, 30% RH; b is the response value of the zinc oxide / in-situ fluorine-doped nickel oxide composite material prepared in Example 4 to 10 ppm of different types of test gases at 200°C, 80% RH.
[0035] Fig.14 This is a schematic diagram of the gas sensor prepared in Example 8 of the present invention. DETAILED DESCRIPTION
[0036] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0037] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0038] In view of the fact that the gas-sensing performance of zinc oxide to nitrogen dioxide is significantly deteriorated under high humidity, the present invention proposes a zinc oxide / in-situ fluorine-doped nickel oxide composite material and a preparation method and application thereof.
[0039] A typical embodiment of the present invention provides a method for preparing a zinc oxide / in-situ fluorine-doped nickel oxide composite material, comprising the following steps:
[0040] Hydroxyzinc fluoride, a nickel source, an alkali source and a surfactant are added to an alcohol solvent, mixed evenly and then subjected to a solvothermal reaction to obtain a hydroxyzinc fluoride / nickel hydroxide precursor, and the hydroxyzinc fluoride / nickel hydroxide precursor is annealed to thermally decompose the hydroxyzinc fluoride / nickel hydroxide precursor to obtain the product.
[0041] The solvent thermal reaction described in the present invention refers to a reaction carried out under closed system conditions, using an organic substance as a solvent, heating the reaction system to produce a gas pressure higher than the atmospheric pressure of the external environment, and performing the reaction under the gas pressure condition.
[0042] The nickel source of the present invention refers to a compound containing nickel, generally a nickel salt. In some embodiments, the nickel source is any one of nickel chloride (NiCl2), nickel nitrate (Ni(NO3)2) or nickel acetate (Ni(CH3COO)2) or a combination thereof.
[0043] In some embodiments, the alkaline source is urea (CH4N2O), hexamethylenetetramine (C6H 12 N4), hexadecyltrimethylammonium bromide (C 19 H 42 BrN) or any one or combination thereof.
[0044] In some embodiments, the surfactant is sodium citrate (C6H5O7Na3), polyvinyl pyrrolidone ((C6H9NO) n ) or ascorbic acid (C6H8O6) or any one or a combination thereof.
[0045] In some embodiments, the molar ratio of hydroxyzinc fluoride to the nickel source, the alkali source, and the surfactant is 1:(0-0.1):(0.03-0.1):(0.03-0.1).
[0046] The alcohol solvent of the present invention can be methanol, ethanol, propanol, isopropanol, etc. In some embodiments, the alcohol solvent is methanol.
[0047] In some embodiments, the solvothermal reaction is carried out at a temperature of 100-200° C. and for a time of 6-24 h.
[0048] In some embodiments, the annealing treatment is performed at a temperature of 300-500° C., for a time of 1-5 h, and at a heating rate of 1-5° C. / min.
[0049] In some embodiments, a zinc source, a fluorine source and an alkali source are added to water and mixed evenly, and then a hydrothermal reaction is performed to obtain hydroxyzinc fluoride.
[0050] The hydrothermal reaction described in the present invention refers to a reaction carried out under the conditions of a closed system, using water as a solvent, heating the reaction system to produce a gas pressure higher than the atmospheric pressure of the external environment, and performing the reaction under the gas pressure condition.
[0051] The zinc source of the present invention refers to a compound containing zinc, generally a zinc salt. In some embodiments, the zinc source is any one of zinc chloride (ZnCl2), zinc nitrate (Zn(NO3)2) or zinc acetate (Zn(CH3COO)2) or a combination thereof.
[0052] The fluorine source of the present invention refers to a compound containing fluorine, generally a salt containing fluorine. In some embodiments, the fluorine source is any one of ammonium fluoride (NH4F), ammonium fluoroborate (NH4BF4) or ammonium hexafluorosilicate ((NH4)2SiF6)) or a combination thereof.
[0053] In some embodiments, the molar mass ratio of the zinc source, the fluorine source and the alkali source is 1:(0.2-0.8):
[0054] (0.5-1.5).
[0055] In some embodiments, the temperature of the hydrothermal reaction is 80-180° C. and the time is 1-24 h.
[0056] The selection range of the alkali source for the hydrothermal reaction and the alkali source for the solvothermal reaction in the present invention is the same.
[0057] Another embodiment of the present invention provides a zinc oxide / in-situ fluorine-doped nickel oxide composite material obtained by the above preparation method.
[0058] In some embodiments, the diameter of the zinc oxide matrix is 8-12 μm, and the zinc oxide matrix is composed of zinc oxide nanorods with a diameter of 70-90 nm.
[0059] In some embodiments, the size of the in-situ fluorine-doped nickel oxide is 4-6 nm.
[0060] A third embodiment of the present invention provides a gas sensing element, including a substrate, a sensing layer is arranged on the surface of the substrate, and the gas sensitive material of the sensing layer is the above zinc oxide / in-situ fluorine-doped nickel oxide composite material.
[0061] In some embodiments, the preparation method is: mixing the gas-sensitive material with a solvent to form a slurry, coating the slurry on the surface of a substrate, and drying.
[0062] In some embodiments, the substrate is a ceramic substrate.
[0063] In some embodiments, the solvent is one of deionized water (H2O), anhydrous ethanol (C2H6O), or a combination thereof.
[0064] In some embodiments, the mass ratio of the gas-sensitive material to the solvent is 1:(2-6).
[0065] In some embodiments, before the slurry is applied to the surface of the substrate, the substrate is dried, specifically, at a drying temperature of 70-100° C. and a drying time of 2-6 min.
[0066] In some embodiments, after the slurry is coated on the substrate surface, the drying temperature is 80-120° C. and the drying time is 8-24 hours. Such conditions are conducive to the complete drying of the slurry on the substrate surface.
[0067] A fourth embodiment of the present invention provides an application of the above zinc oxide / in-situ fluorine-doped nickel oxide composite material or gas sensor in detecting NO2.
[0068] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0069] Example 1
[0070] A method for preparing a flower-shaped hydroxy zinc fluoride precursor material comprises the following steps:
[0071] ZnCl2, NH4F and C6H 12 N4 was dissolved in 70 mL of deionized water at a molar mass ratio of 1:0.51:1, mixed evenly, and then subjected to solvent thermal reaction at 100°C for 2 h under closed conditions. The reaction product was centrifuged, washed, and dried to obtain a hydroxyzinc fluoride precursor.
[0072] Example 2
[0073] A method for preparing a flower-shaped zinc oxide material comprises the following steps:
[0074] Zn(NO3)2, NH4BF4 and C6H 12 N4 was dissolved in 60 mL of deionized water at a molar mass ratio of 1:0.4:1.2, mixed evenly, and then subjected to solvent thermal reaction at 130°C for 18 h under closed conditions. The reaction product was centrifuged, washed, and dried to obtain a hydroxyzinc fluoride precursor.
[0075] The prepared hydroxy zinc fluoride precursor was annealed at 300°C at a heating rate of 1°C / min for 3h to obtain a flower-like zinc oxide material.
[0076] Example 3
[0077] A method for preparing a zinc oxide / in-situ fluorine-doped nickel oxide composite material comprises the following steps:
[0078] Zn(NO3)2, NH4BF4 and C 19 H 42 BrN was dissolved in 50 mL of deionized water at a molar mass ratio of 1:0.8:1.2, mixed evenly, and then subjected to solvent thermal reaction at 95°C for 1 h under closed conditions. The reaction product was centrifuged, washed, and dried to obtain a hydroxyzinc fluoride precursor.
[0079] Dissolve the hydroxy zinc fluoride precursor in 40 mL of anhydrous methanol and disperse evenly. Then, mix the hydroxy zinc fluoride, NiCl2, CH4N2O, (C6H9NO n The molar mass ratio of 1:0.025:0.03:0.03 is uniformly added to the above solvents in sequence. After uniform dissolution, the solution is transferred to a closed condition and subjected to a solvent thermal reaction at 120°C for 6 hours. The reaction product is centrifuged, washed and dried to obtain a hydroxyzinc fluoride / nickel hydroxide precursor.
[0080] The prepared hydroxy zinc fluoride / nickel hydroxide precursor was annealed at 300° C. at a heating rate of 1° C. / min for 2 h to obtain a zinc oxide / in-situ fluorine-doped nickel oxide composite material.
[0081] Example 4
[0082] A method for preparing a zinc oxide / in-situ fluorine-doped nickel oxide composite material comprises the following steps:
[0083] Zn(CH3COO)2, NH4F and C6H 12 N4 was dissolved in 75 mL of deionized water at a molar mass ratio of 1:0.51:1, mixed evenly, and then subjected to solvent thermal reaction at 95°C for 2 h under closed conditions. The reaction product was centrifuged, washed, and dried to obtain a hydroxyzinc fluoride precursor.
[0084] Dissolve the hydroxy zinc fluoride precursor in 30 mL of anhydrous methanol and disperse it evenly. 19 H 42 BrN and C6H5O7Na3 were added to the above solvent in a molar mass ratio of 1:0.05:0.055:0.078 in sequence. After being uniformly dissolved, the solution was transferred to a closed condition and subjected to a solvent thermal reaction at 180°C for 12 hours. The reaction product was centrifuged, washed and dried to obtain a hydroxy zinc fluoride / nickel hydroxide precursor.
[0085] The prepared hydroxy zinc fluoride / nickel hydroxide precursor was annealed at 400°C at a heating rate of 1°C / min for 3h to obtain a zinc oxide / in-situ fluorine-doped nickel oxide composite material.
[0086] Example 5
[0087] A method for preparing a zinc oxide / in-situ fluorine-doped nickel oxide composite material comprises the following steps:
[0088] Dissolve ZnCl2, NH4F and CH4N2O in 30 mL of deionized water at a molar mass ratio of 1:0.2:0.5, mix well, and then perform solvent thermal reaction at 150°C for 12 h under closed conditions. Centrifuge, wash and dry the reaction product to obtain a hydroxy zinc fluoride precursor.
[0089] Dissolve the hydroxy zinc fluoride precursor in 60 mL of anhydrous methanol and disperse evenly. 12 N4, (C6H9NO) n The molar mass ratio of 1:0.075:0.1:0.1 was uniformly added to the above solvents in sequence. After uniform dissolution, the solution was transferred to a closed condition and subjected to a solvent thermal reaction at 100°C for 24 hours. The reaction product was centrifuged, washed and dried to obtain a hydroxyzinc fluoride / nickel hydroxide precursor.
[0090] The prepared hydroxy zinc fluoride / nickel hydroxide precursor was annealed at 500° C. for 2 h at a heating rate of 5° C. / min to obtain a zinc oxide / in-situ fluorine-doped nickel oxide composite material.
[0091] Example 6
[0092] A method for preparing a zinc oxide / in-situ fluorine-doped nickel oxide composite material comprises the following steps:
[0093] Dissolve Zn(NO3)2, (NH4)2SiF6 and CH4N2O in 80 mL of deionized water at a molar mass ratio of 1:0.4:1.5, mix well, and then perform solvent thermal reaction at 80°C for 12 h under closed conditions. Centrifuge, wash and dry the reaction product to obtain a hydroxy zinc fluoride precursor.
[0094] After the hydroxyzinc fluoride precursor is dissolved in 60 mL of anhydrous methanol and evenly dispersed, hydroxyzinc fluoride, Ni(CH3COO)2, CH4N2O, and C6H8O6 are evenly added to the above solvent in a molar mass ratio of 1:0.1:0.08:0.06. After uniform dissolution, the solution is transferred to a closed condition and subjected to solvent thermal reaction at 130°C for 16 hours. The reaction product is centrifuged, washed, and dried to obtain a hydroxyzinc fluoride / nickel hydroxide precursor.
[0095] The prepared hydroxyzinc fluoride / nickel hydroxide precursor was annealed at 450°C for 4 hours at a heating rate of 3°C / min to obtain a zinc oxide / in-situ fluorine-doped nickel oxide composite material.
[0096] Example 7
[0097] A method for preparing a fluorine-free doped nickel oxide / zinc oxide composite material comprises the following steps:
[0098] Zn(CH3COO)2, (NH4)2SiF6 and C6H 12 N4 was dissolved in 40 mL of deionized water at a molar mass ratio of 1:0.2:1.2, mixed evenly, and then subjected to solvent thermal reaction at 120°C for 18 h under closed conditions. The reaction product was centrifuged, washed, and dried to obtain a hydroxyzinc fluoride precursor.
[0099] The prepared hydroxy zinc fluoride precursor was annealed at 400°C for 2 h at a heating rate of 2°C / min to obtain a flower-like zinc oxide material.
[0100] Dissolve the flower-shaped zinc oxide material in 50 mL of anhydrous methanol and evenly disperse it. n The molar mass ratio of 1:0.05:0.05:0.075 was uniformly added to the above solvents in sequence. After being uniformly dissolved, the solution was transferred to a closed condition and subjected to a solvent thermal reaction at 180°C for 24 hours. The reaction product was centrifuged, washed and dried to obtain a zinc oxide / nickel hydroxide precursor.
[0101] The prepared zinc oxide / nickel hydroxide precursor was annealed at 400°C for 3 hours at a heating rate of 2°C / min to obtain a fluorine-free doped nickel oxide / zinc oxide composite material.
[0102] Example 8
[0103] A gas sensor and a preparation method thereof, the gas sensor comprising a ceramic substrate, a platinum wire, a gas sensing material and a gold electrode, the preparation method specifically comprising the following steps:
[0104] The flower-shaped zinc oxide, zinc oxide / in-situ fluorine-doped nickel oxide composite material and fluorine-free doped nickel oxide / zinc oxide composite material prepared in Examples 2-7 were mixed with deionized water in a mass ratio of 1:5 and ground evenly to form a slurry. The resulting slurry was then evenly coated on a ceramic substrate, and the ceramic substrate was placed in an oven at 80°C and dried for 5 minutes before being taken out. After repeating the coating and drying process five times, the ceramic substrate coated with the gas-sensitive material was placed in an oven at 100°C and dried for 12 hours, and a platinum wire was connected to obtain a gas-sensitive element.
[0105] Performance Testing:
[0106] Figure 1 XRD patterns of the hydroxy zinc fluoride precursor, pure zinc oxide and zinc oxide / in-situ fluorine-doped nickel oxide composite material prepared in Examples 1-6 of the present invention; Figure 1 a It can be obtained that the prepared hydroxyzinc fluoride is a pure orthorhombic phase structure. After annealing, hydroxyzinc fluoride is completely transformed into a hexagonal zinc oxide structure, and no hydroxyzinc fluoride precursor remains. As the modification amount of in-situ fluorine-doped nickel oxide increases, XRD shows that the phase structure has no obvious change, indicating that in-situ fluorine-doped nickel oxide will not destroy the phase structure of zinc oxide. Figure 1It can be observed from the XRD magnified spectrum of b that the zinc oxide / in-situ fluorine-doped nickel oxide composites all show NiO-related crystal planes, and all have low-angle offsets compared to the standard diffraction peak positions of NiO. In addition, the offset gradually decreases with the increase of NiO loading, indicating that fluoride ions are doped into the NiO lattice and occupy the lattice gap positions. Since fluoride ions come from the decomposition process of the ZnOHF matrix, the amount of fluoride ions released is limited. Therefore, with the increase of NiO loading, the average doping amount of fluoride ions gradually decreases, and the diffraction peak offset also gradually decreases.
[0107] Figure 2 SEM images of hydroxy zinc fluoride precursor, pure zinc oxide and zinc oxide / in-situ fluorine-doped nickel oxide composite materials prepared in Examples 1-6 of the present invention; it can be seen that the pure hydroxy zinc fluoride precursor prepared in Example 1 exhibits a hexagonal flower-like structure with a size of about 10 μm. The nano flower-like structure is self-assembled by a large number of nanorods, and the diameter of the nanorods is about 80 nm. Pure zinc oxide still exhibits a flower-like structure with no obvious change in size. It is self-assembled by nanorods, which are further stacked by a large number of nanoparticles. A large number of pores are retained between the nanoparticles, which is caused by the release of HF during the decomposition of hydroxy zinc fluoride. After the surface of zinc oxide is further modified with in-situ fluorine-doped nickel oxide, the morphology and structure of the material will not change significantly. At the same time, no obvious nickel oxide-related structure is observed on the surface, proving that nickel oxide grows highly dispersedly on the surface of the zinc oxide matrix.
[0108] Figure 3 TEM, HRTEM and HAADF-STEM spectra of pure zinc oxide and zinc oxide / in-situ fluorine-doped nickel oxide composite materials prepared in Examples 2 and 4 of the present invention; Figure 3 a. Figure 3 In b, it can be observed that pure zinc oxide exhibits a hexagonal snowflake-like morphology with a size of about 10 μm, and is further self-assembled from nanorods stacked with nanoparticles. The diameter of the nanorods is about 80 nm, which is consistent with the SEM results. The central area of the flower-like structure further exhibits a hollow cavity structure, and the characteristic diffraction rings of zinc oxide are calibrated in the selected area electron diffraction. In addition, Figure 3 c1. Figure 3 The interplanar spacings measured in c2 correspond to the (103) and (110) planes of pure zinc oxide, respectively, proving that the synthesized material is zinc oxide; Figure 3 d. Figure 3 As can be seen in Figure e, the morphology and size of the ZnO / in-situ fluorine-doped NiO composite material have not undergone significant changes. In the selected area electron diffraction, in addition to the characteristic diffraction rings of ZnO, additional diffraction rings calibrated to the NiO (012) crystal plane group are also observed. Figure 3 f1, Figure 3The interplanar spacing measured in f2 corresponds to the (101) crystal plane of pure zinc oxide and the (012) crystal plane of nickel oxide, among which the interplanar spacing of nickel oxide is higher than the standard value, which further proves that the interplanar spacing increases due to the doping of fluorine ions in the lattice gap of nickel oxide. Figure 3 From the HAADF-STEM image and element distribution diagram of the zinc oxide / in-situ fluorine-doped nickel oxide composite material in g, it can be observed that Zn, O, Ni, and F are uniformly distributed, proving that the prepared material contains the above elements. Combined with the SEM and XRD analysis results, it can be shown that the prepared material is zinc oxide / in-situ fluorine-doped nickel oxide.
[0109] Figure 4 XPS spectra of pure zinc oxide, zinc oxide / in-situ fluorine-doped nickel oxide composite materials and non-fluorine-doped nickel oxide / zinc oxide composite materials prepared in Examples 2-7 of the present invention; Figure 4 a It can be seen that the zinc ions in the samples exist in a divalent state, and the binding energy positions of the zinc ions in the zinc oxide / in-situ fluorine-doped nickel oxide composites and the fluorine-free nickel oxide / zinc oxide composites are shifted, indicating that there is an electronic interaction between nickel oxide and zinc oxide. Figure 4 The F1s spectrum in b shows that there is no F signal in pure zinc oxide, indicating that the hydroxy zinc fluoride precursor is completely decomposed into zinc oxide. The zinc oxide / in-situ fluorine-doped nickel oxide composite materials prepared in Examples 3-6 show F1s signals, corresponding to the fluoride ion signals doped in nickel oxide. Combined with the pure zinc oxide spectrum, it can be concluded that fluoride ions are only doped in the nickel oxide component. There is also no fluoride ion signal in the fluorine-free doped nickel oxide / zinc oxide composite material prepared in Example 7. Figure 4 The O1s spectrum in c shows that all samples contain adsorbed oxygen, oxygen vacancies and lattice oxygen components in zinc oxide. After loading nickel oxide, lattice oxygen components in nickel oxide appear in the O1s spectrum of the sample, and the signal gradually increases with the increase of nickel oxide loading; Figure 4 The Ni 2p spectrum in d shows that the pure zinc oxide sample prepared in Example 2 does not show relevant signals, proving that the sample does not contain nickel. The zinc oxide / in-situ fluorine-doped nickel oxide composite materials and non-fluorine-doped nickel oxide / zinc oxide composite materials prepared in Examples 3-7 contain Ni 2+ and Ni 3+ The signal proves the existence of multivalent nickel ions.
[0110] Figure 5 The BET-BJH spectra of pure zinc oxide, zinc oxide / in-situ fluorine-doped nickel oxide composite materials and fluorine-free nickel oxide / zinc oxide composite materials prepared in Examples 2, 4 and 7 of the present invention are shown in Figure 1. The specific surface areas of pure zinc oxide, zinc oxide / in-situ fluorine-doped nickel oxide composite materials and fluorine-free nickel oxide / zinc oxide composite materials prepared in Examples 2, 4 and 7 are calculated to be 15.10, 10.75 and 25.15 m2 g -1 The zinc oxide / in-situ fluorine-doped nickel oxide composite material exhibits the lowest specific surface area and porosity, indicating that the in-situ fluorine-doped nickel oxide is uniformly dispersed on the surface of the zinc oxide matrix, thereby forming a more uniform protective layer to prevent the zinc oxide matrix from being disturbed by water molecules or surface hydroxyls, while the fluorine-free nickel oxide / zinc oxide composite material shows a further increase in specific surface area, which significantly increases the area of influence of water molecules on the material, resulting in further deterioration of the material's anti-humidity stability.
[0111] Figure 6 O2-TPD spectra of pure zinc oxide, zinc oxide / in-situ fluorine-doped nickel oxide composite materials and non-fluorine-doped nickel oxide / zinc oxide composite materials prepared in Examples 2, 4 and 7 of the present invention; it can be seen that pure zinc oxide and zinc oxide / in-situ fluorine-doped nickel oxide composite materials show three desorption peaks with similar desorption temperatures. Compared with pure zinc oxide, zinc oxide / in-situ fluorine-doped nickel oxide composite materials do not show a significant increase in oxygen activity, while for the non-fluorine-doped nickel oxide / zinc oxide composite material prepared in Example 7, a new stronger desorption peak is formed at about 216.9°C. In addition, the relative content of weak oxygen adsorption sites (100-150°C) of non-fluorine-doped nickel oxide / zinc oxide composite materials is significantly reduced, indicating that the surface loading of non-fluorine-doped nickel oxide will lead to an increase in the overall chemical adsorption oxygen activity of the material, and the chemically adsorbed oxygen formed inhibits NO2 adsorption, causing the gas-sensitive performance to decrease. In addition, chemically active oxygen will also react with water molecules to form more surface hydroxyls, thereby causing the material's anti-humidity stability to be significantly inhibited. High electronegative fluorine doping can effectively inhibit the chemical adsorption oxygen activity, thereby inhibiting the formation of surface hydroxyls.
[0112] Figure 7 NO2-TPD spectra of pure zinc oxide, zinc oxide / in-situ fluorine-doped nickel oxide composite materials and fluorine-free doped nickel oxide / zinc oxide composite materials prepared in Examples 2, 4 and 7 of the present invention; it can be seen that pure zinc oxide, zinc oxide / in-situ fluorine-doped nickel oxide composite materials and fluorine-free doped nickel oxide / zinc oxide composite materials all contain three NO2 desorption peaks with similar desorption temperatures, indicating that nickel oxide and in-situ fluorine-doped nickel oxide modify zinc oxide without generating new NO2 adsorption sites, that is, NO2 is mainly adsorbed on the zinc oxide matrix, wherein the DI peak with the lowest desorption temperature is the weak NO2 adsorption peak, wherein the number of weak desorption peaks of the fluorine-free doped nickel oxide / zinc oxide composite materials prepared in Example 7 and the zinc oxide / in-situ fluorine-doped nickel oxide composite materials prepared in Example 4 are both higher than that of pure zinc oxide, indicating that the nickel oxide component enhances the adsorption of NO2 by the zinc oxide matrix, and promotes the conversion of the weak NO2 adsorption sites of zinc oxide into strong adsorption sites, thereby enhancing the sensitivity of the material to NO2.
[0113] Figure 8This is the Quasi-XPS spectrum of the zinc oxide / in-situ fluorine-doped nickel oxide composite material prepared in Example 4 of the present invention; Figure 8 In the Zn 2p fine spectrum of a, Zn 2+ The peaks of all shifted toward the lower binding energy direction, indicating that at high temperatures, stronger electron exchange occurred between zinc oxide and in-situ fluorine-doped nickel oxide components, and more free electrons gathered on zinc oxide, thus promoting the NO2 gas-sensing reaction. Figure 8 The F1s fine spectrum of b shows that under room temperature, since the fluorine ions are doped in the lattice gap of nickel oxide, there is only one F1s peak signal. Under the optimal working temperature, two signal peaks appear in F 1s. Due to the violent lattice vibration and mismatch of oxygen vacancies at high temperature, some fluorine ions doped in the lattice gap of nickel oxide migrate to the oxygen ion site of nickel oxide to form substitutional doping. The highly electronegative fluorine ions occupy the surface oxygen ion position, blocking the nickel-oxygen ion bond of nickel oxide, thereby inhibiting the reaction of water molecules and active sites, avoiding the formation of a large number of surface hydroxyl groups, and further improving the material's anti-humidity stability. Figure 8 The O1s fine spectrum of c shows that the amount of lattice oxygen in the nickel oxide component will further increase at the optimal working temperature compared to room temperature, indicating that nickel oxide can exhibit stronger oxygen adsorption capacity at high temperatures. Therefore, the nickel oxide component without fluorine ion dopant protection is more likely to react with water molecules at high temperatures to form surface hydroxyl groups, showing poor anti-humidity stability. Figure 8 It can be seen from the Ni 2p fine spectrum of d that at high temperature, the material Ni 3+ / Ni 2+ The ratio will decrease, which will further promote the formation of chemically adsorbed oxygen, thereby increasing the number of sites that can react with water molecules. At the same time, the enhanced adsorption of oxygen will also inhibit the gas-sensitive reaction of NO2.
[0114] Fig. 9 The response recovery resistance change curves of pure zinc oxide, zinc oxide / in-situ fluorine-doped nickel oxide composite materials and non-fluorine-doped nickel oxide / zinc oxide composite materials prepared in Examples 2-7 of the present invention to 10ppm NO2 at 200°C and 30-80% RH. It can be seen that both the pure zinc oxide material and the non-fluorine-doped nickel oxide / zinc oxide composite materials exhibit unstable NO2 response recovery curves under different relative humidity conditions, indicating their poor humidity resistance stability. A small amount of in-situ fluorine-doped nickel oxide composite zinc oxide exhibits excellent humidity-independent NO2 gas sensing ability. The humidity resistance stability of the material is further reduced after the in-situ fluorine-doped nickel oxide is further improved, which indicates that after the F doping amount is too low, the effect of the dopant on the humidity resistance stability of the nickel oxide component will gradually decrease, indicating that the fluorine dopant effectively improves the humidity resistance stability of the nickel oxide / zinc oxide heterogeneous component.
[0115] Fig.10 The response recovery resistance change curve of the zinc oxide / in-situ fluorine-doped nickel oxide composite material prepared in Example 4 of the present invention to 10ppm NO2 at 100-240°C and 30-80% RH; it can be clearly seen that the response recovery curve of the material hardly changes with the change of relative humidity conditions at different temperatures, indicating that the optimal group of zinc oxide / in-situ fluorine-doped nickel oxide composite materials can achieve excellent humidity resistance stability detection of NO2 under a wide operating temperature and relative humidity range, and the sensor can meet the detection requirements under different working conditions.
[0116] Fig.11 The zinc oxide / in-situ fluorine-doped nickel oxide composite material prepared in Example 4 of the present invention has a response recovery resistance change curve, a response value-concentration relationship and a corresponding fitting curve to 0.1-20ppm NO2 at 200°C, 30% and 80% RH; the zinc oxide / in-situ fluorine-doped nickel oxide composite material can detect NO2 quickly, linearly and accurately, and the NO2 detection limit is 0.1ppm. Under different relative humidity conditions, the best group of zinc oxide / in-situ fluorine-doped nickel oxide composite materials shows almost no change in detection limit, response recovery speed, response value and baseline resistance for NO2 detection, and the response value-concentration relationship and the corresponding fitting curves at different concentrations are almost completely overlapped, which indicates that the material is not affected by ambient humidity for NO2 detection under actual temperature and variable ambient humidity working conditions, and exhibits excellent anti-humidity stability.
[0117] Fig.12 The cyclic curve of the zinc oxide / in-situ fluorine-doped nickel oxide composite material prepared in Example 4 of the present invention to 10 ppm NO2 at 200°C, 30% and 80% RH. The image shows that in five consecutive tests, the response value and response recovery speed of the best group of zinc oxide / in-situ fluorine-doped nickel oxide composite material are almost not affected by the environmental humidity, indicating that the material can continuously, stably and humidity-resistantly detect NO2 in a high humidity environment.
[0118] Fig.13 The response values of the zinc oxide / in-situ fluorine-doped nickel oxide composite material prepared in Example 4 of the present invention to 10 ppm of different types of test gases at 200°C, 30% and 80% RH; it can be seen that the response values of the material to NO2 gas and seven typical interfering gases under different humidity conditions will not change significantly, indicating that the optimal zinc oxide / in-situ fluorine-doped nickel oxide composite material has a humidity-resistant and stable NO2 gas recognition ability.
[0119] Fig.14The gas sensor prepared in Example 8 of the present invention is shown in FIG. The gas sensor includes a ceramic substrate, a gold electrode, four platinum wires and a sensing material. In the preparation process of the gas sensor, the prepared gas-sensitive material is coated on the ceramic substrate, and after uniform coating and drying, the ceramic substrate is welded to the four corner bases through four platinum wires to obtain the gas sensor.
[0120] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a zinc oxide / in-situ fluorine-doped nickel oxide composite material, characterized in that: The steps include: Hydroxyzinc fluoride, a nickel source, an alkali source and a surfactant are added to an alcohol solvent, mixed evenly and then subjected to a solvothermal reaction to obtain a hydroxyzinc fluoride / nickel hydroxide precursor, and the hydroxyzinc fluoride / nickel hydroxide precursor is annealed to thermally decompose the hydroxyzinc fluoride / nickel hydroxide precursor to obtain the product.
2. The method for preparing the zinc oxide / in-situ fluorine-doped nickel oxide composite material according to claim 1, characterized in that: The nickel source is any one of nickel chloride, nickel nitrate or nickel acetate or a combination thereof; Or, the alkali source is any one of urea, hexamethylenetetramine, hexadecyltrimethylammonium bromide or a combination thereof; Or, the surfactant is any one of sodium citrate, polyvinyl pyrrolidone or ascorbic acid or a combination thereof; Alternatively, the molar ratio of hydroxyzinc fluoride to the nickel source, the alkali source, and the surfactant is 1:(0-0.1):(0.03-0.1):(0.03-0.1).
3. The method for preparing the zinc oxide / in-situ fluorine-doped nickel oxide composite material according to claim 1, characterized in that: The alcohol solvent is methanol; Or, the temperature of the solvent thermal reaction is 100-200°C and the time is 6-24h; Alternatively, the annealing temperature is 300-500°C, the time is 1-5h, and the heating rate is 1-5°C / min.
4. The method for preparing the zinc oxide / in-situ fluorine-doped nickel oxide composite material according to claim 1, characterized in that: A zinc source, a fluorine source and an alkali source are added into water and mixed evenly, and then a hydrothermal reaction is carried out to obtain hydroxy zinc fluoride.
5. The method for preparing the zinc oxide / in-situ fluorine-doped nickel oxide composite material according to claim 4, characterized in that: The zinc source is any one of zinc chloride, zinc nitrate or zinc acetate or a combination thereof; Or, the fluorine source is any one of ammonium fluoride, ammonium fluoroborate or ammonium hexafluorosilicate or a combination thereof; Alternatively, the temperature of the hydrothermal reaction is 80-180° C., and the time is 1-24 h.
6. A zinc oxide / in-situ fluorine-doped nickel oxide composite material, characterized in that: Obtained by the preparation method according to any one of claims 1 to 5.
7. The zinc oxide / in-situ fluorine-doped nickel oxide composite material according to claim 6, characterized in that: Zinc Oxide The diameter of the substrate is 8-12 μm, and the zinc oxide substrate is composed of zinc oxide nanorods with a diameter of 70-90 nm; Alternatively, the size of the in-situ fluorine-doped nickel oxide is 4 to 6 nm.
8. A gas sensor, comprising a substrate, a sensing layer being arranged on the surface of the substrate, characterized in that: The gas sensitive material of the sensing layer is the zinc oxide / in-situ fluorine-doped nickel oxide composite material as described in claim 6 or 7.
9. The gas sensor according to claim 8, characterized in that: The preparation method is as follows: a gas-sensitive material is mixed with a solvent to form a slurry, the slurry is coated on the surface of a substrate, and the slurry is dried to obtain the product.
10. Use of the zinc oxide / in-situ fluorine-doped nickel oxide composite material according to claim 6 or 7 or the gas sensor according to claim 8 or 9 in detecting NO2.
Citation Information
Patent Citations
Controllable synthesizing method for hydroxy zinc fluoride nanometer materials with different morphologies and environmental photocatalytic application of hydroxy zinc fluoride nanometer materials
CN109970098A
Semiconductor heterojunction air-sensitive material and preparation method and application thereof
CN110596196A